Association between vitamin D and zoledronate-induced acute-phase response fever risk in osteoporotic patients - Lu, Ke; Shi, Qin; Gong, Ya-qin; Li, Chong (Frontiers in Endocrinology, 2022)
Objectives: To elucidate the independent correlation between vitamin D content and zoledronate (ZOL)-triggered acute-phase response (APR) fever risk in osteoporotic (OP) patients, and to examine the potential threshold for optimal vitamin D concentrations that prevent the occurrence of ZOL-induced fever. Methods: This retrospective investigation was based on a prospectively documented database compiled at the Affiliated Kunshan Hospital of Jiangsu University between January 2015 and March 2022. In total, 2095 OP patients, who received ZOL during hospitalization, were selected for analysis. The primary endpoint was the presence (>37.3°C) or absence (≤37.3°C) of fever, quantified by the maximum body temperature, measured within 3 days of ZOL infusion. The exposure variable was the baseline serum 25-hydroxyvitamin D (25[OH]D) levels. Results: The OP patients with fever exhibited markedly reduced 25(OH)D content than those without fever. Upon adjusting for age, gender, order of infusion of ZOL, main diagnosis, season of blood collection, year of blood collection, calcitonin usage, and beta-C-terminal telopeptide of type I collagen (β-CTX) levels, a 10 ng/mL rise in serum 25(OH)D content was correlated with a 14% (OR, 0.86; 95% CI, 0.76 to 0.98, P-value = 0.0188) decrease in the odds of ZOL-induced fever. In addition, a non-linear relationship was also observed between 25(OH)D levels and fever risk, and the turning point of the adjusted smoothed curve was 35 ng/mL of serum 25(OH)D content. Conclusions: Herein, we demonstrated the independent negative relationship between serum 25(OH)D content and ZOL-induced fever risk. According to our analysis, 25(OH)D above 35 ng/mL may be more effective in preventing ZOL-induced APR. If this is confirmed, a “vitamin D supplemental period” is warranted prior to ZOL infusion, particularly the first ZOL infusion, to ensure appropriate 25(OH)D levels that protect against ZOL-induced fever.